Labor mobility and fiscal policy in a currency union - Baglioni, Angelo; Boitani, Andrea; Bordignon, Massimo (Munich, 2015)
"Labor mobility is commonly taken as a property of an optimal currency area. But how does that property affect the outcome of fiscal policies? In our model, we show that perfect (costless) labour mobility is not necessarily welfare improving, since it prevents the national fiscal authorities from pursuing independent policies, opening the way to a coordination prob-lem. With symmetric shocks, the federal fiscal policy can improve welfare by playing a coordinating role. With asymmetric shocks, the federal policy allows both countries to reach a higher productive efficiency, provided the federal government is endowed with a federal budget."